Teaching Beyond the Classroom: A Phenomenological Study of Fiqh Teachers’ Strategies to Foster Duha Prayer Awareness in a Junior Islamic School - Amalia Ramadhan; Hemawati Hemawati; Indra Satia Pohan (Tinta Emas Institute, 2025)
In Islamic schooling, the sunnah Duha prayer is often promoted as a vehicle for spiritual growth and character formation, yet students’ awareness and regular practice vary widely. This study explores how fiqh teachers translate doctrine into daily habit by nurturing students’ awareness of the Duha prayer within a junior Islamic school setting. Using a qualitative phenomenological approach at MTs Al-Ishlahiyah Binjai, data were gathered through classroom and prayer-time observations, semi-structured interviews with fiqh teachers and students (Grades VII–IX), and document analysis (lesson plans, school worship schedules, attendance logs). Iterative coding and thematic analysis were used to develop an explanatory model of teacher roles. The analysis identifies an actionable 3M+R role set—Modeling (teacher exemplarity and congregational presence), Motivation (spiritual meaning-making, goal-setting, and encouragement), Monitoring (routine checks, gentle reminders, and supportive supervision), and Reinforcement (feedback, recognition, and reflective discussions). These practices work best when embedded in school routines (fixed Duha times, shared spaces, clear expectations) and supported by consistent communication with parents. Students reported clearer understanding of the Duha prayer’s benefits (discipline, focus, emotional calm), increased readiness to participate, and greater regularity of practice. Fiqh teachers can effectively raise students’ awareness and participation in the Duha prayer when pedagogical exemplarity, structured routines, and supportive reinforcement are aligned. The 3M+R framework offers a practical guide for Islamic schools to systematize worship habituation while strengthening students’ spiritual literacy and character.